Public Service Innovation through SIMRS at Daya Regional Public Hospital, Makassar - Anisa Fitri; Sulmiah; Putri Dzakilla Handayani; Nina Agustina; Widyawati (Perkembangan Kajian Sosial, 2026)
This study aims to analyze public service innovation through the Hospital Management Information System (HMIS) at Daya Regional Public Hospital, Makassar. The research focuses on examining how information technology-based innovation is implemented in hospital services and identifying the benefits and challenges of HMIS implementation in supporting healthcare services. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving hospital management staff, healthcare workers, and service users at Daya Regional Public Hospital, Makassar. Data analysis was conducted using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The study used Everett Rogers’ Diffusion of Innovation theory as the analytical framework, focusing on five dimensions: relative advantage, compatibility, complexity, trialability, and observability. The findings indicate that the implementation of HMIS has contributed to improving administrative efficiency, accelerating patient data management, strengthening coordination among hospital units, and creating more organized and integrated healthcare services. The use of digital registration systems, electronic medical records, and integrated service management has improved the effectiveness of public healthcare services. However, the study also found several challenges, including unstable internet networks, limited technological infrastructure, and uneven integration across several service units. The study concludes that the success of information technology-based public service innovation is influenced not only by technological factors but also by organizational readiness, human resources, and infrastructure support in sustaining digital healthcare services.